2020
DOI: 10.1016/j.biocon.2020.108650
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for communicating about bats to prevent persecution in the time of COVID-19

Abstract: While the current COVID-19 pandemic continues to wreak havoc on human health and national economies, conservationists are struggling to prevent misguided persecution of bats, which are misleadingly being blamed for spreading the disease. Although at a global level, such persecution is relatively uncommon, even a few misguided actions have the potential to cause irrevocable damage to already vulnerable species. Here, we draw on the latest findings from psychology, to explain why some conservation messaging may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 79 publications
0
84
0
3
Order By: Relevance
“…Among the most profound examples of human–wildlife disease transmission is the current global COVID‐19 pandemic that is severely affecting public health, society, and the world economy (Chakraborty & Maity, 2020; Messmer, 2020). Evidence suggests bats are a natural reservoir host for the novel coronavirus, SARS‐CoV‐2 (Boni et al., 2020; MacFarlane & Rocha, 2020). Continued urbanization and its resulting expansion of human activities directed at wildlife (e.g., wildlife markets) and use of urban structures by wildlife (e.g., highway underpasses, culverts, buildings) have facilitated increased human–bat urban interactions around the world (Li & Wilkins, 2014; Russo & Ancillotto, 2015).…”
Section: Ecological Drivers Of Conflict and Associated Biological Outmentioning
confidence: 99%
“…Among the most profound examples of human–wildlife disease transmission is the current global COVID‐19 pandemic that is severely affecting public health, society, and the world economy (Chakraborty & Maity, 2020; Messmer, 2020). Evidence suggests bats are a natural reservoir host for the novel coronavirus, SARS‐CoV‐2 (Boni et al., 2020; MacFarlane & Rocha, 2020). Continued urbanization and its resulting expansion of human activities directed at wildlife (e.g., wildlife markets) and use of urban structures by wildlife (e.g., highway underpasses, culverts, buildings) have facilitated increased human–bat urban interactions around the world (Li & Wilkins, 2014; Russo & Ancillotto, 2015).…”
Section: Ecological Drivers Of Conflict and Associated Biological Outmentioning
confidence: 99%
“…Conversely, ‘disease’ articles identified parasites and pathogens, but have yet to demonstrate effects on fitness and thus have little direct utility to conservation. However, ‘disease’ studies may negatively affect public perception of bats if they are inappropriately reported, and we reiterate the crucial role of proper outreach in supporting conservation (MacFarlane & Rocha 2020). Social studies relevant to Japanese bat conservation were rare (only Vincenot et al 2015b, 2017), but this area warrants further research, as human factors often decide conservation outcomes.…”
Section: Discussionmentioning
confidence: 76%
“…Although it is unlikely that traditional media will change their exploitation of sensational events, shifting to a regular coverage of biological invasions, scientists should exploit sensational news to introduce laypeople to biological invasions. The adoption of communication guidelines for traditional media [34] and a tight collaboration between journalists and researchers will be fundamental for this task.…”
Section: Resultsmentioning
confidence: 99%